How to avoid the risk of maladaptation? From a conceptual understanding to a systematic approach for analyzing potential adverse effects in adaptation actions - Oscar Higuera Roa; Yvonne Walz; Udo Nehren (Mitigation and Adaptation Strategies for Global Change, 2025)
Climate change is already affecting and altering natural and human systems, and its effects are expected to intensify over the coming decades. Adaptation is therefore imperative for future development. However, like any other anthropogenic intervention, adaptation measures can have unintended detrimental impacts and adverse effects on human and natural systems, known as maladaptation. With growing evidence of maladaptation, practitioners in the fields of resilience and climate change adaptation increasingly focus on avoiding maladaptation risks in their projects. Yet, there is still no clear understanding of how to comprehensively and systematically analyze adverse effects in adaptation actions. To address this gap, this article advances the conceptual understanding of maladaptation and elaborates a pragmatic approach for examining, identifying, and diagnosing maladaptation risks in adaptation measures. Starting by breaking down the concept of maladaptation into analytical components (i.e., drivers, mechanisms, dimensions, attributes, forms, and outputs of maladaptation) based on the relevant literature, we propose a new harmonized and actionable definition. Based on this new understanding, we propose a practical and systematic approach to analyze maladaptation risks at the early stages of adaptation planning. Through the proposed definition, conceptual disaggregation, and practical framework, this paper contributes to a better understanding of maladaptation and provides practitioners with means to improve the design of future adaptation measures.
Keywords: 330; Maladaptation; Adaptation planning; Risk analysis; Framework; Climate change adaptation